Mobilizing sustainable energy – the importance of rural regions, small units and energy villages - Girgibo, Nebiyu; Peura, Pekka; Haapanen, Ari (Springer, 2026)
Small rural regions, termed energy villages, are potentially self-sufficient, due to the renewable energy sources harvestable nearby, and most such villages would be able to produce further energy or raw materials, energy for sale outside their region. In many areas, bioenergy would suffice to cover the demand for all energy (electricity, heating, transport, agriculture etc.), and overall in all research areas, bioenergy potential corresponds to some 1/3 of the consumption of energy. Wind and solar power could thus make regions over-productive. The same applies to larger regions, consisting of multiple small villages. An increasing number, rural areas are capable in covering the energy demand cities within the region, including the industries there. The economic potential is vast. The values used here were estimated before the Russian–Ukrainian war, therefore, is not possible currently to provide an accurate current value, other than to estimate that prices and the entire economic value of energy will increase. Also, and as this is not a technical planning document, it has not been possible to analyze more precisely single separate or systemic regional solutions. Our paper presents and discusses the logical framework within which rural regions are crucial in the process of sustainable energy transition.
Keywords: Energy Village concept; Renewable energy; Jepua; LEAP-RE; Energy consumption; Energy potential; fi=VEBIC|en=VEBIC|; fi=Markkinointi|en=Marketing|